Balloon Cell Urethral Melanoma: Differential Diagnosis and Management - M. McComiskey; C. Iavazzo; M. Datta; R. Slade; B. Winter-Roach; G. Lambe; V. K. Sangar; M. Smith (Hindawi Limited, 2015)
Introduction. Primary malignant melanoma of the urethra is a rare tumour (0.2% of all melanomas) that most commonly affects the meatus and distal urethra and is three times more common in women than men. Case. A 76-year-old lady presented with vaginal pain and discharge. On examination, a 4 cm mass was noted in the vagina and biopsy confirmed melanoma of a balloon type. Preoperative CT showed no distant metastases and an MRI scan of the pelvis demonstrated no associated lymphadenopathy. She underwent anterior exenterative surgery and vaginectomy also. Histology confirmed a urethral nodular malignant melanoma. Discussion. First-line treatment of melanoma is often surgical. Adjuvant treatment including chemotherapy, radiotherapy, or immunotherapy has also been reported. Even with aggressive management, malignant melanoma of the urogenital tract generally has a poor prognosis. Recurrence rates are high and the mean period between diagnosis and recurrence is 12.5 months. A 5-year survival rate of less than 20% has been reported in balloon cell melanomas along with nearly 20% developing local recurrence. Conclusion. To the best of our knowledge, this case is the first report of balloon cell melanoma arising in the urethra. The presentation and surgical management has been described and a literature review provided.